MEDIA SOCIAL MARKETING FOR SEO AND SMO POSITIONING - Gavilánez Alvarez, Oscar Danilo; Hachi Mancero, Cristina Belén; Aguilar Cajas, Héctor Oswaldo; Pazmiño Garzón, Denise Liliana (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
The purpose of the article is the application of social media marketing in the marketing actions of a company, improving its positioning in the market, the Red Market Supermarkets company of the city of Riobamba was considered as a case study, since the company does not count with adequate insertion in the digital area; Market research was carried out based on the PEA and the TCP of Riobamba to calculate the sample, with the results obtained it was determined that the supermarkets with the best positioning in the city are TIA and AKI stores that constitute chains of supermarkets nationwide; locally, the supermarket AHÍ ES, while RED MARKET SUPERMERCADOS presents a non-significant positioning. Finally, the proactive framework was made based on digital marketing strategies and the use of digital platforms that allow improving the positioning of the company. It is concluded that the development of infographics through flashy, innovative and personalized content generate harmonious relationships with customers getting fans for the company, allowing traffic and possible conversion of customers to the business website and social networks, achieving SEO and SMO positioning.